Review of Aderidae Csiki, 1909 (Insecta: Coleoptera) of Cabo Verde - Telnov, Dmitry; Gompel, Nicolas (Zootaxa, 2021)
The Aderidae (Coleoptera: Tenebrionoidea) of Cabo Verde (or Cape Verde in English transcription) Archipelago in the Central Atlantic Ocean is revised based on an examination of types and additional material. Four species are confirmed for the archipelago, three of the genus Cobososia Collado et Alonso-Zarazaga, 1996 and one of the genus Aderus Stephens, 1829. We also propose to transfer Anthicus reductus Wollaston, 1867 (Anthicidae: Anthicinae: Anthicini) to the genus Cobososia (Aderidae), as Cobososia reducta (Wollaston, 1867) comb. nov. and demonstrate, that Cobososia angulithorax (Desbrochers des Loges, 1881) is conspecific with Cobososia reducta (Wollaston, 1867) syn. nov. Finally, we present new records and an illustrated identification key to the ant-like leaf beetles of Cabo Verde.